PENGARUH PENERAPAN STRATEGI PEMBELAJARAN JOYFUL LEARNING TERHADAP HASIL BELAJAR MATEMATIKA PADA MATERI BANGUN DATAR KELAS III SD INPRES 130 TAROWANG KABUPATEN JENEPONTO - Hatmawati, Hatmawati; Safei, Safei; Dian Angriani, Andi; Rosdiana, Rosdiana (Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2022)
This study aims to determine whether there is an effect of implementing joyful learning learning strategies on student learning outcomes in third grade mathematics at SD Inpres 130 Tarowang, Jeneponto Regency. The type of research used in this study is the type of research One Group pretest-posttest. Data collection in this study using tests and observations. Data were analyzed using descriptive statistical techniques and inferential statistics. The results of the analysis show that the application of the joyful learning strategy has an effect on mathematics learning outcomes for third grade students of SD Inpres 130 Tarowang, Jeneponto Regency. In addition, learning mathematics with a joyful learning strategy can improve the quality of mathematics learning, namely increasing the comfort of students during learning, increasing student activity and increasing interest in participating in mathematics learning.